Reading poetry a complete coursebook - Furniss, Tom; Bath, Michael (Routledge, 2022)
"Reading Poetry offers a comprehensive and accessible guide to the art of reading poetry. Discussing more than 200 poems by more than 100 writers and ranging from ancient Greece and China to the 21st century, the book introduces readers to the skills and the critical and theoretical awareness that enable them to read poetry with enjoyment and insight. This third edition has been significantly updated in response to current developments in poetry and poetic criticism and includes many new examples and exercises and new chapters on 'world poetry' and 'eco-poetry' and a greater emphasis throughout on American Poetry, including the impact traditional Chinese poetry has had on modern American poetry. The seventeen carefully staged chapters constitute a complete apprenticeship in reading poetry, leading readers from specific features of form and figurative language to larger concerns with genre, intertextuality, Caribbean poetry, world poetry and the role poetry can play in response to the ecological crisis. The workshop exercises at the end of each chapter, together with an extensive glossary of poetic and critical terms, as well as the number and range of poems analysed and discussed, 122 of which are quoted in full, make Reading Poetry suitable for individual study or as a comprehensive self-contained textbook for university and college classes"--